MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR IPA SISWA MELALUI METODE PICTURE AND PICTURE PADA KONSEP DAUR HIDUP - Rumini - (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2015)
Class action research (CAR) is intended to describe the cooperative learning model with the method of picture and picture that is able to enhance IPA learning results students of SDN Tanjungrejo on the concept of life cycle. Research subjects consisted of 20 students grade IV SDN Tanjungrejo, Loceret, Nganjuk. Data are collected through observations, tests, notes field, and special notes from students in need special. Results of analysis showed that the use of cooperative learning model with the method of picture and picture is able to create an good atmosphere of active learning and fun and are able to improve student learning outcomes achieved degrees of success learning until you reach 90,16%. KEYWORD: active, sains’s study achievement, cooperative model’s, and picture and picture method’s